2 - Visibility, Credibility, Prestige: Evaluating the Implications of Indexing African Journals - Elizabeth Le Roux (Africa Media Review, 2006)
Start-up problems for a journal include attracting authors and building initial readership, but challenges further down the line include building visibility and maintaining credibility. One of the key strategies in this regard is indexing. According to the literature, the main reasons for having a journal indexed or listed in an abstracting service relate to visibility, and to quality, in terms of credibility and prestige. In this paper, I will look at each of these in more detail. For concrete examples, I will draw upon my experience with indexing an interdisciplinary journal in the social sciences, Africa Insight, of which I am currently the editor. Our experience, in a nutshell, has been that getting the journal indexed does create more visibility, and that it certainly confers some credibility – but it has had little effect on the bottom-line of subscriptions and sales.